Enhanced heat transfer efficiency of PTSC using hydromagnetic cross nanofluid: A hydrogen energy application. (29th May 2022) - Minnam Reddy, Vasudeva Reddy; Reddy, M. Girinath; Dinesh, P.A.; Sandeep, N.
Abstract: Nowadays, the foremost thermal source from the sun is solar energy. The current study deals with the enhanced heat transfer of Parabolic Trough Solar Collector (PTSC) using thermic radiation, space-dependent heat source, and nanotechnological energy. For this, we considered water-based graphene oxide (GO) and alumina alloy (AA7075) mixtures flow through PTSC fitted inside the solar wings of aircraft (Fig. 1). A theoretical Maxwell nano model is adopted by incorporating the thermic radiation and space-dependent heat source/sink effects in the energy equation. The pressure drop caused by the fluid-solid interactions is evaluated by introducing the Darcy-Forchheimer condition. The modeled problem is resolved numerically by applying suitable similarities. The impact of various physical constraints on flow and thermal fields are estimated for water-GO and water-GO-AA7075 fluids and found that water-GO-AA7075 hybrid nanoliquid effectively enhances the thermal performance of PTSC in the presence of thermic heat. Darcy-Forchheimer parameter effectively regulates the momentum and energy fields of hybrid nanoliquid. Highlights: Enhanced heat transfer efficiency of Parabolic Through Solar Collector (PTSC). Usage of solar power for energy storage applications. The Darcy-Forchheimer condition evaluates pressure drop caused by the fluid-solid interactions. Water-GO-AA7075 hybrid nanoliquid effectively enhances the thermal performance of PTSC in the presence of thermal radiation. A nanotechnology application for hydrogen energy storage.